Theory-based modifications of an advanced notification letter improves screening for bowel cancer in men: A randomised controlled trial. (September 2016) - Zajac, Ian T.; Duncan, Amy C.; Flight, Ingrid; Wittert, Gary A.; Cole, Stephen R.; Young, Graeme P.; Wilson, Carlene J.; Turnbull, Deborah A.
Abstract: Rationale: Male participation in screening for bowel cancer is sub-optimal. Theory-based interventions provide a means of improving screening uptake. Objective: To test the efficacy of modifying consumer invitation material in line with continuum and stage theories of health behaviour on screening participation. Methods: N = 9216 Australian men aged 50–74 years were randomised to one of four trial arms in a 2 × 2 factorial design randomised controlled trial. Participants received either standard invitation material (control group), or combinations of modified advance-notification and invitation letters. A subsample completed baseline and endpoint behavioural surveys. Results: Participants who received the modified advance notification letter were 12% more likely to screen than those who received the standard version ( RR = 1.12, χ 2 (1) = 10.38, p = 0.001). The modified invitation letter did not impact screening uptake ( RR = 0.97, χ 2 (1) = 0.63, p = 0.424). No significant changes in psychological variables due to the intervention were observed. Conclusion: Modifications to advance notification letters in line with health behaviour theories significantly improves screening uptake in men. Trial registration: Australian New Zealand Clinical Trials Registry: ACTRN12612001122842https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=362688 . Highlights: Biennial screening is effective for reducing the impact of Bowel Cancer. Screening rates in Australia are sub-optimal and particularly problematic in Males. This RCT in 9216 men tested theory-based modifications to invitation material. Modified advance notification letters significantly improved screening rates. Modified invitation letters had no effect on screening uptake.